The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1254/jjp.75.347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Specific Cysteinyl Leukotriene Antagonist, Pranlukast, on Antigen-Induced Cysteinyl Leukotriene-Mediated Rhinitis in Guinea Pigs

Abstract: ABSTRACT-To examine the effects of a specific cysteinyl leukotriene (cysLT) antagonist, pranlukast, on allergic rhinitis, antigen-induced rhinitis in guinea pigs was modified by pretreatment with an cyclo oxygenase inhibitor (indomethacin) followed by an H1-blocker (pyrilamine). Intranasal ovalbumin (OVA) administration in actively sensitized guinea pigs resulted in concentration-dependent increases in nasal permeability and nasal airway resistance (NAR). Although pyrilamine (1 mg/kg, i.v.) abolished these ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…It has been reported by researchers in the laboratories of the manufacturer of pranlukast that 10 -30 mg/ kg pranlukast caused potent inhibition in in vivo experiments of CysLT-mediated allergic reactions (21,22). The present result is different from clinical findings, in which not only the CysLT antagonist montelukast (18,19), but also the 5-lipoxygenase inhibitor zileuton (23) improved nasal function after aspirin administration in aspirin-sensitive asthmatics.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It has been reported by researchers in the laboratories of the manufacturer of pranlukast that 10 -30 mg/ kg pranlukast caused potent inhibition in in vivo experiments of CysLT-mediated allergic reactions (21,22). The present result is different from clinical findings, in which not only the CysLT antagonist montelukast (18,19), but also the 5-lipoxygenase inhibitor zileuton (23) improved nasal function after aspirin administration in aspirin-sensitive asthmatics.…”
Section: Discussioncontrasting
confidence: 82%
“…On the other hand, regarding the allergic rhinitis model of guinea pigs, there is only one study evaluating effects of indomethacin on nasal allergy (21). Fujita et al (21) showed that indomethacin enhanced antigen-induced increase in nasal airway resistance, and the amplified response was inhibited by a treatment with pranlukast (10 mg / kg). However, there is no report that showed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that histamine, leukotrienes, and thromboxane, are involved in the mechanism of development of allergic rhinitis in guinea pigs [6,9,10,[12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…After the waiting period, warm air was again blown into the nasal cavity and the antigen solution was eliminated from the nasal cavity. The nasal airway resistance was measured for 45 min after the antigen challenge, because (1) usually it has been determined for about 30 min in studies in the acute allergic rhinitis model [11,12,14,15] ; (2) such studies suggest that the resistance is still increased at 45 min, and (3) it is diffi cult to anesthetize guinea pigs with pentobarbital for a longer time. At the end of the assessment of the nasal airway resistance, the animal was euthanized by injection of an excessive amount of pentobarbital.…”
Section: Measurement Of Nasal Airway Resistance Induced By Antigen Chmentioning
confidence: 99%
See 1 more Smart Citation